A prospective, multicenter, international study to explore the effect of three different amplitude settings in female subjects with urinary urge incontinence receiving interstim therapy. Issue 3 (1st March 2021) - Elterman, Dean; Ehlert, Michael; De Ridder, Dirk; McCrery, Rebecca; Pakzad, Mahreen; Kaufman, Melissa R.; Shah, Sagar; Margolis, Eric; Bukkapatnam, Raviender; Johnson, Gayle; Zirpel, Lance; Stolen, Kira; et al.
Abstract: Aims: The aim of this study is to evaluate the effect of sub‐sensory amplitude settings of sacral neuromodulation therapy on overactive bladder symptoms in subjects with urinary urge incontinence. Methods: Subjects who qualified for a neurostimulator device implant were randomized to one of three amplitude settings (50% of sensory threshold [ST], 80% of ST, and ST). Subjects completed urinary voiding diaries (3‐day), International consultation on incontinence modular questionnaire—overactive bladder symptoms quality of life questionnaire, and patient global impression of improvement (PGI‐I) to assess change in voiding symptoms and quality of life (QoL) from baseline through 12 weeks. Results: Forty‐eight subjects had a successful test stimulation, 46 were implanted with a neurostimulator device and 43 completed the 12‐week follow‐up visit. The change from baseline to 12 weeks is −3.0 urinary incontinence (UI) episodes/day (95% confidence interval [CI]: −4.4 to −1.7) for the 50% of sensory threshold group, −2.9 UI episodes/day (95% CI: −4.7 to −1.2) for 80% of sensory threshold group, and −3.6 UI episodes/day (95% CI: −5.2 to −1.9) for the sensory threshold group. In each randomized group, improvements were observed in health‐related QoL, its subscales, and symptom interference. Subjects across all three randomization groups reported on the PGI‐I that their bladder condition was better at 12 weeks compared to before they were treated with InterStim therapy. Conclusion: These findings provide insights into possible advancements in the postimplantation phase of therapy with potential for improved patient comfort and increased device longevity.